REFLECTIVE PRACTICE IN LANGUAGE TEACHING - Irene Leong Yoke Chu; Mardziah Hayati Abdullah (The English Teacher, 2007)
The value of reflection in education has long been recognised, particularly by Schon (1987), who revitalised the concept of reflection in today’s educational setting. Reflec- tive practice helps teachers, including ESL teachers, reach a deeper understanding of their own teaching style and efforts and, ultimately, attain greater effectiveness as a teacher. However, the manner and quality of reflection is not always looked into so that it can be of greatest benefit to teachers. This paper considers two tools or models that can help teachers engage in deeper levels of reflection and reach greater awareness of themselves. Moon’s (1999) Two-stage Model and Scharmer’s (2007) Presencing Model may be used as toolkits by language teachers to think about what they are doing, and to actively work towards improving their professional growth.